Lift or drag? Let's get skeptical about freestyle propulsion - Sanders, R. (Sportscience)
Sceptical discussion of the of whether propulsion in freestyle swimming is due primarily to lift or drag. Conclusion: In this example, many of us were quick to accept theory as fact before sufficient evidence was available. It may still be too early to state that freestyle propulsion is dominated by drag, but the commonly held belief that it is dominated by lift may be ill-founded and incorrect.